2001
DOI: 10.1017/s147292880100005x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic organization in thalamocortical neurons and state-dependent functions of inhibitory synaptic inputs

Abstract: GABA-ergic thalamic reticular neurons function generically or singularly in a state-dependent manner: during quiet sleep they synchronously and rhythmically inhibit thalamocortical neurons (TCNs) via bursts, thereby eliciting the low-threshold Ca 2+ potentials in TCNs that are crucial to oscillatory network behavior in the thalamo-reticulo-cortical system; during wakefulness they shape the flux of ascending sensory information by inhibiting TCNs with asynchronous and arrhythmic single-spikes. To investigate ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 19 publications
5
7
0
Order By: Relevance
“…A white‐noise study would more completely characterize passive electrical properties, but would not be as readily interpretable in a neurobiological context. However, we agree with Neubig & Destexhe (2001) that a study of biologically relevant signals is more readily interpreted and more readily extended to the active‐dendrite case.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…A white‐noise study would more completely characterize passive electrical properties, but would not be as readily interpretable in a neurobiological context. However, we agree with Neubig & Destexhe (2001) that a study of biologically relevant signals is more readily interpreted and more readily extended to the active‐dendrite case.…”
Section: Methodssupporting
confidence: 88%
“…This meant that, while a synaptic signal generated anywhere in a thalamocortical cell dendrite would be transmitted throughout the arbor and to the soma, it was concluded that distal dendrites of interneurons were functionally isolated from the soma and other dendrites, suggesting that each interneuron might consist of many independent dendritic domains. The thalamocortical cell aspect of this study has been superseded by the findings of Neubig & Destexhe (2001).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In each TC, EPSP soma from different dendritic locations had very similar peak amplitude with a coefficient of variation (CV) of only 12% on average (see also Neubig & Destexhe, 2001; Briska et al 2003). Furthermore, the different TCs were also very similar to each other; the mean EPSP soma varied only 24% between the different TCs.…”
Section: Resultsmentioning
confidence: 99%